The Message of the Jerusalem Council in the Acts of the Apostles : A Linguistic Stylistic Analysis - Dawson, Zachary K. (Linguistic Biblical Studies, 2022)
By applying a stylistic analysis within a systemic-functional linguistic framework, this study argues that Luke's construal of the Jerusalem Council in Acts 15 and its co-thematic passages attempt to persuade Jewish believers of Luke's audience not to separate from multi-ethnic churches, a goal that is accomplished through subverting the value orientations of a prominent Noahic tradition within Second Temple Jewish literature that promotes strict Jewish isolation from Gentiles. As a result, this study breaks fresh methodological ground in the linguistic study on the New Testament and also advances critical scholarship on the book of Acts.